How sensory properties of food affect human feeding behavior - Rolls, B; Rowe, E; Rolls, E (Pergamon Press, 1982)
The sensory properties of food which can lead to a decrease in the pleasantness of that food after it is eaten, and to enhanced food intake if that property of the food is changed by successive presentation of different foods, were investigated. After eating chocolates of one color the pleasantness of the taste of the eaten color declined more than of the non-eaten colors, although these chocolates differed only in appearance. The presentation of a variety of colors of chocolates, either simultaneously or successively, did not affect food intake compared with consumption of the subject's favorite color. Changes in the shape of food (which affect both appearance and mouth feel) were introduced by offering subjects three successive courses consisting of different shapes of pasta. Changes in shape led to a specific decrease in the pleasantness of the shape eaten and to a significant enhancement (14%) of food intake when three shapes were offered compared with intake of the subject's favorite shape. Changes in just the flavor of food (i.e. cream cheese sandwiches flavored with salt, or with the non-nutritive flavoring agents lemon and saccharin, or curry) led to a significant enhancement (15%) of food intake when all three flavors were presented successively compared with intake of the favorite. The experiments elucidate some of the properties of food which are involved in sensory specific satiety, and which determine the amount of food eaten.